Parasitism by Tylenchid Nematodes in Natural Populations of Pintomyia fischeri (Diptera: Psychodidae: Phlebotominae) in Argentina - Fernández, María Soledad (2015)
Fil: Fernández, María Soledad. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Medicina Tropical; Argentina.